Female underrepresentation in the cybersecurity workforce – a study on cybersecurity professionals in Sri Lanka. (26th January 2022) - Withanaarachchi, Amila; Vithana, Nisansala
Abstract : Purpose: This study aims to identify factors impacting female underrepresentation among cybersecurity professionals in Sri Lanka. Design/methodology/approach: The study is based on survey data from 75 female professionals working in the cybersecurity sector of Sri Lanka. Partial least squares structural equation modelling was used to analyse the data. Findings: Results showed that female self-efficacy on their capabilities, family, organisational culture, mentors and role model act as antecedents for women's perceived motivation to select cybersecurity as a career option. Originality/value: The study advances the literature on workforce gaps in the cybersecurity sector and claims that there is no single factor causing significant female underrepresentation in the cybersecurity industry. While clarifying the complexity of such factors, the study presents how such factors can systematise to attract females into the cybersecurity field.